Identification of high diverse heterotic groups in sunflower inbred lines for further hybrid production - Avin, F.A.; Nabipour, A.; Zali, A.; Shahbazi, P.; Arockiaraj, J.; Bhassu, S. (The Gaurav Society of Agricultural Research Information Centre (GSARIC), 2013)
Sunflower (Helianthus annuus L.) as a source of vegetable oil and proteins is grown in many parts of the world. It is the fourth important vegetable oil crop, producing 9 million tonnes per year. The present study was attempted to identify the effective mating partners and assign probable heterotic groups by estimating the genetic variation among the experimental materials. In order to evaluate the genetic diversity of 49 sunflower promising inbred lines, selected morphological features as well as oil percentage were precisely investigated. Sunflower stocks including 18 R-lines and 31 B-lines were planted based on a simple lattice (7 × 7) design with two replications. Relationships among (i) quantitative and quantitative; (ii) qualitative and quantitative; and (iii) qualitative and qualitative traits were estimated by correlation analysis, ANOVA and chi square test, respectively. Results of ANOVA revealed significant differences (P<0.01) between the lines for most of the characters. A considerable outcome appeared when negative correlation between oil percentage and seed weight was achieved. Classification of lines based on cluster analysis separated them into two distinct groups of male and female. These achievements were confirmed by plot analysis based on the first two principal components. Moreover, the results of factor analysis indicated that four factors could explain 73.92% of the total variance. To sum up, the high genetic diversity that was demonstrated among 49 sunflower inbred promising lines suggested that selection of parents for hybridization needed to be based on genetic diversity. According to these findings, the heterotic groups that may lead the crosses to production of vigour hybrids were recommended.